Perawatan Tubuh pada Hari Jumat dalam Al Kutub As Sittah : (Kajian Tematik Hadis) - Khairatul Nisa; Afdilla Nisa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research highlights Islam's concern for health, particularly the aspect of taking care of the body on Friday. Hadiths in al-Kutub as-Sittah recommend practices such as bathing, using a tooth-stick, wearing perfume, and wearing the best clothes. Sunan Ibn Majah's hadith mentions bathing, dressing in the best clothes, and wearing perfume, while Muslim's narration adds tooth-stick. This study aims to understand the status and understanding of these traditions to provide theoretical and practical benefits. Using the literature research method with a thematic approach (maudhui), the analysis begins with the takhrij of the hadith using the book al-Mu'jam al-Mufahras li Alfadz al-Hadith. The research assesses the quality of the hadith as hasan, but because it is supported by Sahih Bukhari and Muslim, it rises to shahih lighairihi. An understanding of the Hadith shows the importance of maintaining cleanliness and respect for Friday through bathing such as taking a janabah bath, using a toothbrush, wearing fragrances to boost confidence, and wearing the best clothes. Friday is considered special, so taking care of the body according to the Prophet's guidance is a form of respect for it.